2014
DOI: 10.1111/cobi.12323
|View full text |Cite
|
Sign up to set email alerts
|

Potential Negative Ecological Effects of Corridors

Abstract: Despite many studies showing that landscape corridors increase dispersal and species richness for disparate taxa, concerns persist that corridors can have unintended negative effects. In particular, some of the same mechanisms that underlie positive effects of corridors on species of conservation interest may also increase the spread and impact of antagonistic species (e.g., predators and pathogens), foster negative effects of edges, increase invasion by exotic species, increase the spread of unwanted disturba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 56 publications
1
58
0
1
Order By: Relevance
“…However, potential negative impacts of high connectivity are still a subject of discussion. For example, Haddad et al (2014) found no evidence that corridors increase unwanted disturbances or invasions of non-native species. The dynamics of complex ecosystems are determined by the interaction between slow variables, e.g., soil organic matter and water-holding capacity, and fast variables, e.g., soil mineral nitrogen and water flow.…”
Section: Principles and Examples For Enhancing Ecosystem Servicesmentioning
confidence: 97%
“…However, potential negative impacts of high connectivity are still a subject of discussion. For example, Haddad et al (2014) found no evidence that corridors increase unwanted disturbances or invasions of non-native species. The dynamics of complex ecosystems are determined by the interaction between slow variables, e.g., soil organic matter and water-holding capacity, and fast variables, e.g., soil mineral nitrogen and water flow.…”
Section: Principles and Examples For Enhancing Ecosystem Servicesmentioning
confidence: 97%
“…Regardless, although connectivity might facilitate the spread of invasive species and disease or increased disturbance, improved habitat connectivity is a net positive conservation outcome (Hannah et al, 2002;Shafer, 2014). Moreover, Haddad et al (2014) found no broad evidence to support the possible undesirable side-effects of increased habitat connectivity and further suggested that wider corridors and softer corridor edges could ameliorate potential negative impacts.…”
Section: Introductionmentioning
confidence: 97%
“…The linkages between rural multifunctionality, landscape connectivity and invasive species are in only early stages of investigation (With 2002;Haddad et al 2014). This is surprising, given the obvious mechanistic similarity between NNGs and other agents of landscape fragmentation documented in this paper, viz.…”
Section: Discussionmentioning
confidence: 80%
“…1e-g), through construction of water management features, livestock exclusion, and revegetation (Ludwig and Tongway 1996). Large multi-value areas can play a vital role in preserving landscape biodiversity Hobbs 1999, Smith et al 2013), but even when spatially restricted they can buffer remnant native vegetation and provide supplementary habitat for native species, a process known as ''matrix softening'' (Haddad et al 2014). Following from this model, management practices that increase the conservation and agro-economic values of a given MRL simultaneously (Fig.…”
Section: A Multifunctional Rural Landscape Modelmentioning
confidence: 99%